Studi Komparatif Edukasi Diet Sehat Dengan Latihan Fisik Terhadap Monitoring Gula Darah Pada Penderita Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Darussalam Medan - Fitriani Harefa; Novarasi Melina Silitonga (STIKES Columbia Asia Medan, 2026)
Type 2 diabetes mellitus (t2dm) is a chronic disease caused by insulin resistance and insufficient insulin production, resulting in elevated blood glucose levels. Proper blood glucose control can prevent both microvascular and macrovascular complications of diabetes. Effective management is therefore needed to monitor blood glucose levels through healthy lifestyle modifications, including a healthy diet and physical exercise. This study aimed to determine the difference between healthy diet education and physical exercise in monitoring blood glucose levels among patients with t2dm at darussalam public health center, medan. This quantitative study employed a quasi-experimental two-group pretest-posttest design. The population consisted of 294 patients with t2dm, from which 44 participants were selected using purposive sampling. Data were collected using an observation sheet to record blood glucose levels among patients with t2dm. The data were analyzed using paired t-test and independent t-test. The results showed a significant difference in blood glucose levels between the healthy diet education and physical exercise groups, with a p-value of 0.000 (p < 0.05). The healthy diet education intervention resulted in a decrease in blood glucose levels of 23.86 mg/dl, while the physical exercise intervention resulted in a mean decrease in blood glucose levels of 52.72 mg/dl. There was a difference of 28.86 mg/dl in the change in blood glucose levels between the healthy diet education and physical exercise groups, with a p-value of 0.000. It can be concluded that there was a significant difference between healthy diet education and physical exercise interventions in monitoring blood glucose levels. It is recommended that the public health center establish regular physical exercise programs and strengthen support for dietary management by developing a non-communicable disease prevention community through healthy lifestyle programs. Posbindu health cadres are expected to serve as facilitators in implementing these programs.